Risk Shifting and Long-Term Contracts : Evidence from the Ras Gas Project - Dailami, Mansoor; Hauswald, Robert (World Bank, Washington, DC, 2014)
Risk shifting and incomplete contracting lie at the heart of the agency relationship inherent in the procurement and financing of large-scale projects such as power plants, oil and gas pipelines, and liquefied natural gas (LNG) facilities. Resolving this agency problem is critical in structuring the nexus of long-term contracts--construction, operating, output sale, and financial contracts--commensurate with the project's underlying tehcnological and market organization. By investigating the Ras Gas bonds--the largest and most liquid global project bonds ever issued in an emerging market economy--the authors provide empirical evidence of the risk-shifting consequences of contractual incompleteness. They relate the credit spreads of Ras Gas bonds to the bond spreads of the Korea Electric Power Company (Kepco), the major customer, in the context of a 25-year supply agreement, the oil price index used to price the LNG, emerging debt market returns, and various systematic and unsystematic risk variables. Consistent with theoretical predictions, they find that the risk factors affecting the sales and purchase agreements drive perceptions of market risk for Ras Gas bonds. In particular, Ras Gas yield spreads reflect the market's risk assessment of Kepco. Other priced risks are energy price and foreign currency exposure (which influence Ras Gas credit spreads through their impact on Kepco), Korean economic variables, and spillovers from turbulence in European and Latin American emerging debt markets. The authors' analysis shows that the design of each contractual arrangement is not independent, because risk factors relevant to one contract determine the price and risk premium of the other. Despite heavy capitalization and partial guarantees by the parent companies of Ras Gas, the off-take agreement essentially determines the riskiness of the bonds. The authors interpret this as evidence of the nexus-of-contracts view of the firm in the presence of contractual incompleteness: Investors bear all residual risks and price their financial claims accordingly.